Biological Activities of Zinc Oxide Nanoparticles Green Synthesized Using the Aqueous Extract of Dracocephalum kotschyi Boiss - Mirzania, Foroogh; Salimikia, Iraj; Ghasemian Yadegari, Javad; Marzban, Abdolrazagh; Firouzi, Amirmasoud; Nazarzadeh, Alireza; Aalaei, Javid (Current Drug Discovery Technologies, 2024)
Background: Dracocephalum kotschyi Boiss. is known as a native medicinal plant of Iran. Objective: In this study, aqueous extract of D. kotschyi was used to synthesize ZnO-NPs. To produce ZnO-NPs, aerial parts of D. kotschyi were powdered and then macerated for obtaining aqueous extract, after that, aqueous extract was used to reduse zinc nitrate to ZnO-NPs. Methods: To confirm nanoparticles synthesis, SEM, TEM, UV-Vis, FTIR, and XRD were used. The synthesized ZnO-NPs were studied for antimicrobial activities by microdilution method for calculating MIC and MBC. Analysis of ZnO-NPs confirmed successful synthesis by extract of D. kotschyi. Results: The sizes of ZnO-NPs were estimated 50-200 nm in diameter. Antibacterial and antifungal experiments showed potent activities against Staphylococos aureus, Pseudomonas aeruginosa and Candida albicans. The results of the studies showed that the nanoparticles synthesized with the aqueous extract of D. kotschyi have a much greater antimicrobial effect than the aqueous extract of D. kotschyi and zinc nanoparticles, each alone (MIC values 3.7 to 7.5 mg/ml). Conclusion: The noteworthy point is that the inhibitory rate of synthesized zinc oxide nanoparticles is higher compared to broad-spectrum antibiotics, such as chloramphenicol (MIC values 15 mg/ml). Determining the therapeutic and toxic dose of this product for humans requires further investigation and clinical trials.
Keywords: Staphylococos aureus